Konsep Pendidikan Karakter Dalam Perspektif Hadits - Zulvan Maulana; M. Luthfi Munir; Septian Khoirul Umam; Bahrudin Yusuf; Ahmad Hadiq Syifa Al Fawaz (Tabsyir: Jurnal Dakwah dan Sosial Humaniora, 2024)
Character education is to instill certain character at once, giving the seeds so that learners are able to cultivate its distinctive character at the time into the life of the community. By taking some ideas or models will not make the character become creative participants, but requires a mature concept was able to grow the character of students. One concept of character education that have long been made by the Prophet through the Hadith-hadith. The concept of character education that is described in the hadith the Prophet is very important to be developed and studied. As for the quality of the hadith about the concept of character education is of sanad become Shahih li zatihi, as well as valid in terms of honor. While the concept of character education in the hadith there are two. First, the establishment of which is based on the exemplary character will reap goodness for himself and others. Therefore, the influence of family as the first school for the children should be good ones anyway. Secondly, in the view of Islam, man is born in this world bring the nature, potential, basic abilities, or nature (heredity).